Chilean Pipunculidae (Diptera) key to genera, new records, description of a new species of Eudorylas aczel and a catalog of species - Rafael, J.A.=700 1 Ale Rocha, R.
(Es, En)
Ilus., 25 ref.
Keywords: DIPTERA; TAXONOMIA; REGISTRO; ESPECIES NUEVAS; CHILE; EUDORYLAS; PIPUNCULIDAE; REVISTA CHILENA DE ENTOMOLOGIA